2018
DOI: 10.19080/adoh.2018.08.555749
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Desensitizing Effect of a Toothpaste & Mouthwash- Containing Potassium Nitrate: An In Vivo & In Vitro Scanning Electron Microscopic Study

Abstract: Potassium Nitrate has been used as a desensitizing agent to treat dentinal hypersensitivity for quite a long time. The effectiveness of a potassium nitrate is evaluated many times in the form of toothpaste. There hasn't been much study done to evaluate the desensitizing efficacy of potassium nitrate used in the form of mouthwash. Aim of our study was to compare the desensitizing effect of a tooth paste & mouthwash-both containing Potassium Nitrate.Material & Methods: Thirty patients were assessed using evapora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“… Elias-Boneta et al in 2013 in a randomized, double-blinded, parallel single-center clinical study concluded that mouth rinse containing arginine provided a superior reduction in DH compared to potassium nitrate and a negative control mouthwash after 2 weeks[ 154 ] Sharda et al, 2018 compared effectiveness of a desensitizing dentifrice and mouthwash containing calcium sodium phosphosilicate on DH and found the mouthwash to be as effective as the toothpaste in reducing DH and with a fair remineralization potential[ 155 ] Sen et al, 2018 also compared effectiveness of a desensitizing dentifrice and mouthwash containing potassium nitrate on DH and found the mouthwash to be as effective as the toothpaste in reducing DH[ 156 ] Sharma et al determined the efficacy in relieving dentinal sensitivity of 4 weeks’ treatment with an alcohol-free mouth rinse comprising 1.4% potassium oxalate compared with negative and positive controls. The findings revealed a decreased sensitivity by 110% in the positive-control subjects versus negative-control subjects ( P < 0.001), and no serious treatment-related oral adverse events were seen in any of the study subjects.…”
Section: Classification Of Desensitizing Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“… Elias-Boneta et al in 2013 in a randomized, double-blinded, parallel single-center clinical study concluded that mouth rinse containing arginine provided a superior reduction in DH compared to potassium nitrate and a negative control mouthwash after 2 weeks[ 154 ] Sharda et al, 2018 compared effectiveness of a desensitizing dentifrice and mouthwash containing calcium sodium phosphosilicate on DH and found the mouthwash to be as effective as the toothpaste in reducing DH and with a fair remineralization potential[ 155 ] Sen et al, 2018 also compared effectiveness of a desensitizing dentifrice and mouthwash containing potassium nitrate on DH and found the mouthwash to be as effective as the toothpaste in reducing DH[ 156 ] Sharma et al determined the efficacy in relieving dentinal sensitivity of 4 weeks’ treatment with an alcohol-free mouth rinse comprising 1.4% potassium oxalate compared with negative and positive controls. The findings revealed a decreased sensitivity by 110% in the positive-control subjects versus negative-control subjects ( P < 0.001), and no serious treatment-related oral adverse events were seen in any of the study subjects.…”
Section: Classification Of Desensitizing Agentsmentioning
confidence: 99%
“…Sen et al, 2018 also compared effectiveness of a desensitizing dentifrice and mouthwash containing potassium nitrate on DH and found the mouthwash to be as effective as the toothpaste in reducing DH[ 156 ]…”
Section: Classification Of Desensitizing Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, macroscopically, the normal tooth and a hypersensitive tooth have the same dentin, but the difference lies in the symptoms, which suggest minor inflammation of pulp. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…The occlusion of dentinal tubules is caused by the use of physical or chemical substances externally on denuded surfaces, which creates an artificial layer on the outer surface of dentinal tubules by depositing an obliterating material on the dentin surface and reducing the diameter of tubules, blocking dentinal fluid diffusion, and resulting in a decrease in DH. [ 4 ] Various agents are used for treating DH, including lasers, desensitizing dentifrices, mouthwash formulations, dentin sealing agents, periodontal soft tissue grafting, etc. However, no treatment modality has been regarded as the gold standard treatment of dental hypersensitivity.…”
Section: Introductionmentioning
confidence: 99%